2003
DOI: 10.1002/ange.200390030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonds around M(μ‐O)2M Rhombs: Stabilizing a {CoIII(μ‐O)2CoIII} Complex at Room Temperature

Abstract: cysteine-containing dipeptides in high yield and without significant loss of chirality at the C2-exomethine carbon atom. Finally, the application of this method to one-pot tandem dehydrocyclizations afforded a thiazole±thiazoline product in good overall yield and with excellent stereocontrol. Experimental SectionGeneral procedure for synthesis of thiazolines: Trifluoromethanesulfonic anhydride (50 mL, 0.3 mmol) was added slowly to a solution of triphenylphosphane oxide (167 mg, 0.6 mmol) in dry CH 2 Cl 2 (2 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…S6†). This redox couple is more negative than that for cobalt complexes supported by salen 8 a ( E 1/2 = +0.25 V vs. NHE), porphyrin 8 b ( E 1/2 = +0.68 V vs. NHE), corrole 8 c ( E 1/2 = +0.03 V vs. NHE), 1,1′-(ethane-1,2-diyl)bis(3- tert -butylurea) 4 a ( E 1/2 = –0.086 V vs. NHE), and 2,2′,2′-nitrilo-tris( N -isopropylacetamide) 4 b ( E 1/2 = +0.44 V vs. NHE) ligands.…”
Section: Resultsmentioning
confidence: 76%
“…S6†). This redox couple is more negative than that for cobalt complexes supported by salen 8 a ( E 1/2 = +0.25 V vs. NHE), porphyrin 8 b ( E 1/2 = +0.68 V vs. NHE), corrole 8 c ( E 1/2 = +0.03 V vs. NHE), 1,1′-(ethane-1,2-diyl)bis(3- tert -butylurea) 4 a ( E 1/2 = –0.086 V vs. NHE), and 2,2′,2′-nitrilo-tris( N -isopropylacetamide) 4 b ( E 1/2 = +0.44 V vs. NHE) ligands.…”
Section: Resultsmentioning
confidence: 76%
“…6.31) [81]. We found that high-spin [Co(II)(H 2 bade) 2 ] 2-reacts with excess dioxygen to initially produce a species that is formulated as a monomeric cobalt-dioxygen species based on its spectroscopic properties.…”
Section: Dinuclear Cobalt-l-superoxo Complexesmentioning
confidence: 94%
“…[1] Moreover, such studies can lead to the discovery of novel species [2] exhibiting reactivity patterns different from their homodinuclear counterparts. The illustrative example (Scheme 1 inset) is the recently reported [L 1 Ni(μ-O) 2 Cu(MeAN)] + ( 1; L 1 = [HC(CMeNC 6 H 3 ( i Pr) 2 ) 2 ]; MeAN = N,N,N ′ ,N ′ ,N ″-pentamethyl dipropylenetriamine), [3] complex which, in sharp contrast to the presence of electrophilic oxido groups in symmetric [M 2 (μ–O) 2 ] n+ (M = Ni, Co, Fe and Mn) analogues, [4] possesses nucleophilic oxido ligands and deformylates aldehydes.…”
mentioning
confidence: 99%
“…Furthermore, the fully symmetric [L 1 Ni III (μ-O) 2 Ni III L 1 ] 2+ ( 3 ) complex demonstrates a nucleophilic property, which is in contrast to the observed electrophilic behavior of all homodinuclear bis(μ-oxido) cores reported to date. [4] This together with the self-decay of the heterodinuclear [L 1 Ni(μ-O) 2 CoL 3 ] species 2 (L 3 = [HC(CHNC 6 H 3 ( i Pr) 2 ) 2 ]) by an unprecedented hydroxylation mediated 1,3-migration of an aryl-nitrogen atom, represent a novel domain for high-valent bis(μ-oxido)dimetal reactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation